RESOLUTION: Reconfigurable Systems for Mobile Local Communication and Positioning - Tragas, Philippos; Kalis, Antonis; Papadias, Constantinos; Ellinger, Frank; Eickhoff, Ralf; Ußmüller, Thomas; Mosshammer, Ralf; Huemer, Mario; Dabek, Alexander; Doumenis, Dimosthenes; Kounoudes, Anastassios (Mobile and Wireless Communications Summit, 2007)
RESOLUTION aims at developing a wireless three-dimensional (3-D) local positioning system with measurement accuracy in the centimetre regime and real-time ability. A novel frequency modulated continuous wave (FMCW) radar principle with pulsed active reflector is employed. This High-Precision-Localisation-System (HPLS) will be implemented together with common WLAN systems that are used for data communication purposes. Due to its high data rate capabilities and large potential bandwidth, the 802.11a/n standard allocated bandwidth around 5.5 GHz is applied. Special emphasis is given to the system's reconfigurability by efficiently using inherent synergies between the WLAN system and the HPLS approach. To allow multifunctional tasks, highly integrated system on chip (SoC) frontends will be designed on advanced CMOS or BiCMOS technology. Smart power and adaptive performance control will be applied to minimise the power consumption according to application needs. In order to enhance performance and coverage range, the transceiver features adaptive antenna combining (AAC) in the radio frequency (RF) receiver. AAC significantly decreases the power consumption, size and costs, since the number of multiple components is reduced to a minimum. Because of the high 3-D resolution and real-time ability, which can be achieved in indoor environments with strong multipath effects and fading, novel local positioning applications, e.g. for smart factories, robotics, interactive guiding, object tracking and augmented reality are presumably leading to a large economic potential.
elib2cris::1512001600,tragas2007a
Keywords: Adaptive Antenna Combining; High-Precision Localisation-System; voltage controlled oscillator